2016
DOI: 10.1186/s40478-016-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic and lysosomal defects in human tauopathies: analysis of post-mortem brain from patients with familial Alzheimer disease, corticobasal degeneration and progressive supranuclear palsy

Abstract: IntroductionThe accumulation of insoluble proteins within neurons and glia cells is a pathological hallmark of several neurodegenerative diseases. Abnormal aggregation of the microtubule-associated protein tau characterizes the neuropathology of tauopathies, such as Alzheimer disease (AD), corticobasal degeneration (CBD) and progressive supranuclear palsy (PSP). An impairment of the lysosomal degradation pathway called macroautophagy, hereafter referred to as autophagy, could contribute to the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(164 citation statements)
references
References 78 publications
7
143
0
3
Order By: Relevance
“…Thus, these protein homeostasis mechanisms may function differently to affect diverse pathological symptoms in familial vs. sporadic AD. In support of this notion, recent studies have demonstrated that familial AD bearing more mitochondrial unfolded protein response (mtUPR) gene activation (around 70%–90%) compared to sporadic AD (around 40%–60%), indicating that at least mtUPR is more relevant in pathogenesis of familial AD (Piras, Collin, Grüninger, Graff, & Rönnbäck, 2016). …”
Section: Introductionmentioning
confidence: 94%
“…Thus, these protein homeostasis mechanisms may function differently to affect diverse pathological symptoms in familial vs. sporadic AD. In support of this notion, recent studies have demonstrated that familial AD bearing more mitochondrial unfolded protein response (mtUPR) gene activation (around 70%–90%) compared to sporadic AD (around 40%–60%), indicating that at least mtUPR is more relevant in pathogenesis of familial AD (Piras, Collin, Grüninger, Graff, & Rönnbäck, 2016). …”
Section: Introductionmentioning
confidence: 94%
“…Similarly, in a drosophila model of tauopathy, neurodegeneration can still be seen in the absence of neurofibrillary tangle formation (Wittmann et al , 2001). Interestingly, It has been hypothesized that one reason oligomeric tau is able to accumulate in tauopathies is due to the fact that both oligomeric tau and cleaved forms of tau, which have an increased propensity for aggregation compared to full-length tau, are preferentially degraded via autophagy (Chesser et al , 2013), a pathway reported to be defective in tauopathies (Piras et al , 2016) and TBI (Sarkar et al , 2014). Although proteasome dysfunction, the mechanism which preferentially degrades monomeric tau, has also been reported to occur following TBI due to mechanisms such as oxidative stress (Bader and Grune, 2006; Weih et al , 2001; Yao et al , 2008), monomeric full-length tau has a decreased propensity to aggregate compared to cleaved tau (Chesser et al , 2013) and is less toxic than oligomeric tau (Spires-Jones et al , 2011).…”
Section: The Tau Protein – Functions and Dysfunctionsmentioning
confidence: 99%
“…Em condições normais, a tau é predominantemente expressa em axônios neuronais, cuja função principal é promover a montagem de microtúbulos e estabilização, o que é importante para a manutenção do transporte axonal e integridade neuronal Caracteriza-se por distúrbios neurodegenerativos em que a tau é depositada no cérebro. Há diferentes morfologias de agregados de tau observadas, incluindo emaranhados neurofibrilares, astrocitos tufados (TAs), corpos enrolados e linhagens patológicas (Ishiki, et al, 2017;Piras, Collin, Grüninger, Graff, & Rönnbäck, 2016).…”
Section: Fisiopatologia Da Pspunclassified
“…Outro processo referido na literatura trata-se da agregação intracelular anormal e a acumulação da proteína tau associada aos microtúbulos que envolve o conjunto de doenças degenerativas coletivas de desordens neurodegenerativas, dentre elas, a PSP, mas que ainda não são compreendidas, mas se sugere que há modificações pós-translacionais anormais, tais como hiperfosforilação e acetilação, e degradação prejudicial de tau por meio dos sistemas ubiquitina-proteassoma (UPS) e autofagia-lisossoma (Piras, Collin, Grüninger, Graff, & Rönnbäck, 2016).…”
Section: Fisiopatologia Da Pspunclassified
See 1 more Smart Citation